Interface‐ and Surface‐Engineered PdO−RuO2 Hetero‐Nanostructures with High Activity for Hydrogen Evolution/Oxidation Reactions. Issue 9 (8th April 2021) - Samanta, Rajib; Mishra, Ranjit; Barman, Sudip
Abstract: Active catalysts for HER/HOR are crucial to develop hydrogen‐based renewable technologies. The interface of hetero‐nanostructures can integrate different components into a single synergistic hybrid with high activity. Here, the synthesis of PdO−RuO2 −C with abundant interfaces/defects was achieved for the hydrogen evolution reaction (HER) and hydrogen oxidation reaction (HOR). It exhibited a current density of 10 mA cm −2 at 44 mV with a Tafel slope of 34 mV dec −1 in 1 m KOH. The HER mass activity was 3 times higher in base and comparable to Pt/C in acid. The stability test confirmed high HER stability. The catalyst also exhibited excellent HOR activity in both media; in alkaline HOR it outperformed Pt/C. The exchange current density i 0, m of PdO−RuO2 /C was 522 mA mg −1 in base, which is 58 and 3.4 times higher than those of Pd/C and Pt/C. The HOR activity of PdO−RuO2 /C was 22 and 300 times higher than those of PdO/C in acid and base. Improvement of HER/HOR kinetics in different alkaline electrolytes was observed in the order K + <Na + <Li +, and increase of HER as well decrease of HOR kinetics was observed with increasing Li + concentration. It was proposed that OHad ‐M + ‐(H2 O) x in the double‐layer region could influence HER/HOR activity in base. Based on the hard and soft acid and base (HSAB) theory, the OHads ‐M + ‐(H2 O) x could help to remove more OHads into the bulk, leading to increase in HER/HOR activity in alkaline electrolyte (K + <Na + <Li + ) and increasing the HER with increasing Li + concentration. The decrease of HOR activity of PdO−RuO2 /C with increasing M + was due to M + ‐induced OHads destabilization through the bifunctional mechanism. The high HER/HOR activity of PdO−RuO2 /C could be attributed, among other factors, to interface engineering and strong synergistic interaction. This work provides an opportunity to design oxide‐based catalysts for renewable energy technologies. Abstract : Bifunctional electrocatalyst : Synthesis of PdO−RuO2 −C with abundant interfaces/defects is achieved for the hydrogen evolution reaction (HER) and hydrogen oxidation reaction (HOR). It exhibits a current density of 10 mA cm −2 at 44 mV with a Tafel slope of 34 mV dec −1 in 1 m KOH. The high HER/HOR activity of PdO−RuO2 /C can be attributed to interface engineering and strong synergistic interaction.